Implementasi Wakaf Sebagai Polis Asuransi Syari’ah Melalui IPLAN (Insurance Protection Linked Auto Navigation) Syari’ah Generali Sidoarjo - Nur Chamid; Popy Tria Febriati (Management of Zakat and Waqf Journal (MAZAWA), 2020)
Waqf is one of the instruments that must be empowered productively and to the maximum extent possible, one of which is the insurance policy waqf imposed by the MUI DSN in October 2016 which is expected to help the government in its efforts to alleviate poverty and prosper the people. With that PT.Asuransi Jiwa Generali Indonesia formed an institution, namely the Indonesian Waqf Movement (GWI) to expand the network and knowledge of the public regarding sharia insurance policy waqf products through outreach and training to the public. The purpose of this study is to describe (1) the strategy of implementing waqf as an insurance policy through IPLAN Syari'ah Generali, (2) supporting and inhibiting factors in managing waqf as an insurance policy through IPLAN Syari'ah Generali, (3) developing strategies for waqf as an insurance policy. through IPLAN Syari'ah Generali. This research method uses a qualitative approach method. Data collection techniques with observation, interviews and documentation. Data analysis techniques in this study include (1) data reduction (2) data presentation (3) conclusions. The results of the research are as follows: (1) management of productive waqf with cash waqf through insurance waqf products (2) when the policyholder dies 45% of the funds will be donated and the rest is given to the heirs (3) first, supporting factors, establishing the Indonesian Waqf Movement institution to help promote waqf in Indonesia by inviting and socializing the community for waqf. Second, the inhibiting factor, namely the lack of public understanding of cash waqf. (4) the waqf funds from the policy holder will be donated to the waqf management institution which will be developed professionally, namely the Dhuafa Wallet Institute.